1981
DOI: 10.1139/v81-054
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of some bicyclo[2.2.2]oct-5-en-2-ones and bicyclo[2.2.2]octan-2-ones. Rearrangements accompanying oxidative decarboxylation with lead tetraacetate

Abstract: . Can. J. Chem. 59,344 (1981). I-Methoxy-2-methyl-1,4-cyclohexadiene (3), 2-methoxy-I-methyl-1.3-cyclohexadiene (2), and 2-methoxy-1,5,5-trimethyl-1,3-cyclohexadiene (14) on heating with maleic anhydride give 1-methoxy-endo-7-methylbicyclo[2.2.2]oct-5-ene-syn-2,3-dicarboxylic acid anhydride (7) and its 6-methoxy-I-methyl(16a) and 6-methoxy-l,8,8-trimethyl(l6b) analogues, respectively. On hydrolysis 16a and 16b give the corresponding keto dicarboxylic acids, 18a and 18b, via keto anhydrides 17a and 17b. During… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…1 H NMR (CDCl 3 ) δ 1.14 (d, J = 6.5 Hz, 3H), 1.28 (s, 3H), 4.02 (q, J = 6.5 Hz, 1H), region between 5.32 and 5.4 severe overlap between 11 and 12 , 5.92 (dd, J = 11, 17.7 Hz, 1H), 8.27 (bs, 1H). S*R*‐3‐hydroperoxy‐3‐methyl‐4‐penten‐2‐ol ( 12 ). 1 H NMR (CDCl 3 ) δ 1.14 (d, J = 6.6 Hz, 3H), 1.34 (s, 3H), 3.99 (q, J = 6.6 Hz, 1H), region between 5.32 and 5.4 severe overlap between 11 and 12 , 5.99 (dd, J = 11.2, 17.7 Hz, 1H), 8.35 (bs, 1H).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 H NMR (CDCl 3 ) δ 1.14 (d, J = 6.5 Hz, 3H), 1.28 (s, 3H), 4.02 (q, J = 6.5 Hz, 1H), region between 5.32 and 5.4 severe overlap between 11 and 12 , 5.92 (dd, J = 11, 17.7 Hz, 1H), 8.27 (bs, 1H). S*R*‐3‐hydroperoxy‐3‐methyl‐4‐penten‐2‐ol ( 12 ). 1 H NMR (CDCl 3 ) δ 1.14 (d, J = 6.6 Hz, 3H), 1.34 (s, 3H), 3.99 (q, J = 6.6 Hz, 1H), region between 5.32 and 5.4 severe overlap between 11 and 12 , 5.99 (dd, J = 11.2, 17.7 Hz, 1H), 8.35 (bs, 1H).…”
Section: Methodsmentioning
confidence: 99%
“…The allylic hydroperoxides were identified by reduction with triphenylphosphine to the diols followed by comparison to published proton and carbon NMR of these compounds. cis ‐3‐methylene‐1,2‐cyclohexandiol (16‐OH) , (10) trans ‐3‐methylene‐1,2‐cyclohexandiol (16‐OH) (10), cis ‐3‐methyl‐3‐cyclohexen‐1,2‐diol (18‐OH) (11), 3‐methyl‐2,3‐epoxy‐cyclohexanone ( 21 ) (12). Spectral data for the trans ‐1,2‐diol, trans ‐3‐methyl‐3‐cyclohexen‐1,2‐diol (19‐OH) is not available but it is tentatively assigned on the basis of comparison of 13 C NMR chemical shifts in the reaction mixture and comparison with those published for 18‐OH (11).…”
Section: Methodsmentioning
confidence: 99%
“…However, to highlight the specificity of such an event, it is clearly substrate-dependent in that many other 1,2-diketones, including our own for the model yunnaneic acid core, do not undergo such facile dimerization when exposed to silica gel. Finally, in what is an example of a yunnaneic acid A-type dimerization, Yates and Langford showed that treatment of diketone 57 with 0.5 equiv of MeLi could afford 58 , which then reacted with the remaining 57 in solution to afford mixed dimer 59 in 21% yield. Thus, this precedent provided a conceptual underpinning for what we hoped to achieve for the heterodimerization needed in our case.…”
Section: Resultsmentioning
confidence: 99%